Dynamics of cell polarity in tissue morphogenesis: A comparative view from Drosophila and Ciona [version 1; referees: 2 approved] - Veeman, Michael T.; McDonald, Jocelyn A. (My University, 2017)
Tissues in developing embryos exhibit complex and dynamic rearrangements that shape forming organs, limbs, and body axes. Directed migration, mediolateral intercalation, lumen formation, and other rearrangements influence the topology and topography of developing tissues. These collective cell behaviors are distinct phenomena but all involve the fine-grained control of cell polarity. Here we review recent findings in the dynamics of polarized cell behavior in both the Drosophila ovarian border cells and the Ciona notochord. These studies reveal the remarkable reorganization of cell polarity during organ formation and underscore conserved mechanisms of developmental cell polarity including the Par/atypical protein kinase C (aPKC) and planar cell polarity pathways. These two very different model systems demonstrate important commonalities but also key differences in how cell polarity is controlled in tissue morphogenesis. Together, these systems raise important, broader questions on how the developmental control of cell polarity contributes to morphogenesis of diverse tissues across the metazoa. © 2016 Veeman MT and McDonald JA.
Citation: Veeman, M. T., & McDonald, J. A. (2016). Dynamics of cell polarity in tissue morphogenesis: A comparative view from Drosophila and Ciona [version 1; referees: 2 approved]. F1000Research, 5. doi:10.12688/F1000RESEARCH.8011.1